Social media hook sports events: a systematic review of engagement (Communication & Society, 2023)
Social media are nowadays used in all sectors, and likewise frequently within the sports industry. However, there is a lack of studies that offer a holistic understanding of the phenomenon of social media engagement (SME) in this area. Thus, the main object of the present study was the elaboration of a systematic review of the existing literature of the past ten years about SME within the field of sports events. The study was carried out following the PRISMA guidelines. By searching the databases Web of Science, Scopus, ProQuest, and Academic Search Ultimate, we identified 208 studies. After screening and reviewing for eligibility, we finally included 28 articles in the present study. The methodologies, types of analysis applied, main objectives, and the results on SME of the articles included in the synthesis were systematically reviewed. The findings showed that only four articles had as a principal theme the SME. Social media offer a useful tool for engagement, but SME adopts must still gain greater recognition. The need to co-create with users and engage them on social media, due to the great utility of social media in this sector is highlighted based on the results. It was found that SME around sports events remains an emerging and still developing research field which presents a wide range of future research lines.